Evaluation of demographic features of acute drug poisoning with Benzodiazepines; a cross – sectional study - Sanei, Soheil; Shahrbaf, Mohammad Amin; Pajoomand, Abdolkarim; Zamani, Nasim; Daneshmand, Mojdeh; Pouriran, Ramin; Ziai, Seyed Ali (Student Research in Translational Medicine, 2019)
Background: Poisoning is one of the important social problems in developing countries, and acute poisoning due to suicide by drug overdose or toxins is one of the most common cases of poisoning that requires emergency care. This study was aimed to determine the demographics of benzodiazepines poisoned patients in one of the referral centers for poisoning in Iran. Materials and Methods: This cross-sectional study was conducted on patients who referred to the poisoning emergency ward of Loghman Hakim Hospital from April 2015 to March 2016. Among 10624 patients who referred to the hospital at the study period, 2543 of them were poisoned by benzodiazepines. A total of 263 patients were selected randomly and were assessed for age, gender and the type of the benzodiazepine. The data were analyzed by version 15 of SPSS software. Results: Among 263 patients, 127 were males (48.2%) and 136 were females (51.7%). The mean age of patients was 31 years old with a range of 13 – 80 years old. In addition, most patients were in the age of between 18 to 35 years (n = 152). In this study, 91 patients (34.6%) were single-drug poisoned with benzodiazepines and 172 cases (65.4%) were poisoned by multi-drug regimens including benzodiazepines. Between different types of benzodiazepines, the most common type was Alprazolam and the least common benzodiazepine was Oxazepam. Almost 96% of patients (n = 252) were treated successfully and 8 patients (3%) got discharged with self-consent. Furthermore, the mortality rate was approximately 1% (n = 3). Conclusion: Benzodiazepines poisoning is common in younger patients; thus, close attentions are needed for the prescription of these drugs in young patients. Considering easy access to benzodiazepines in the community, periodic visits to psychiatrists may be useful for the reduction of benzodiazepine poisoning.